Alpine dams - Alain Marnezy (Revue de Géographie Alpine)
Mountain reservoirs were initially built in the Alps to meet energy needs in the winter. A certain diversification in the uses of water then gradually developed, related to tourism development in the local communities. Today, the use of facilities belonging to EDF (French Electricity Authority) to provide water for winter resorts to make artificial snow represents a new phase. By taking water from EDF resources to supply snow-making equipment, resort managers are thus able to avoid the problems related to the construction and management of small headwater dams. This new orientation in the use of mountain water resources already affects a number of alpine regions such as the Upper Maurienne valley and Beaufortain massif and represents a renewed form of the territorial integration of water resources.